American Cockroach, Periplaneta americana (Linnaeus) (Insecta: Blattaria: Blattidae) - K. A. Barbara (EDIS)
The American cockroach, Periplaneta americana (Linnaeus), is the largest of the common peridomestic cockroaches measuring on average 4 cm in length. It occurs in buildings throughout Florida especially in commercial buildings. In the northern United States the cockroach is mainly found in steam heat tunnels or large institutional buildings. The American cockroach is second only to the German cockroach in abundance. This document is EENY-141, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 2000.